Strategi Kepala Sekolah dalam Meningkatkan Kompetensi Guru Pai di SMA Miftahul Ulum Ambunten Sumenep - Muhammad Mohlis (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2018)
Head masters as teacher staff function to lead shools which cunduct education especially in the teaching and learning process. As institution manager, they have an important role such as designer, organizer, staff education, and school supervisor. Taecher as educator transfers knowledge to students. They have experience about their profesion, by this way, they create smart students. As transformator, they plant faith, pious, and causing students to have good moral and autonomous students. The research result show that head master strategy in increasing PAI teacher competece of SMA Miftahul Ulum Ambunten Sumenep are in the field of: a) head master strategy, b) school programs, c) head master role, and d) conducting many changes. The supporting factors are human resources who have higher motivation and work seriously in developing their competence, good facilities for learning, then the obstacles factors are the less of fund or donationn to provide facility in moment time.